The Singapore Personal Data Protection Act and an assessment of future trends in data privacy - CHIK, Warren B. (Institutional Knowledge at Singapore Management University, 2013)
In the first part of this paper, I will present and explain the Singapore Personal Data Protection Act (“PDPA”) in the context of legislative developments in the Asian region and against the well-established international baseline privacy standards. In the course of the above evaluation, reference will be made to the national laws and policy on data privacy prior to the enactment of the PDPA as well as current social and market practices in relation to personal data. In the second part of this paper, I will decipher and assess the future trends in data privacy reform and the future development of the privacy regime in Singapore and beyond. In the course of this analysis, international standards, technological trends and recent legal developments in other jurisdictions will be considered.